Mechanisms and dynamics of the NH+2 + H+ and NH+ + H+ + H fragmentation channels upon single-photon double ionization of NH3. (19th November 2020) - Larsen, Kirk A; Rescigno, Thomas N; Streeter, Zachary L; Iskandar, Wael; Heck, Saijoscha; Gatton, Averell; Champenois, Elio G; Severt, Travis; Strom, Richard; Jochim, Bethany; Reedy, Dylan; Call, Demitri; et al.
Abstract: We present state-selective measurements on the N H 2 + + H + and NH + + H + + H dissociation channels following single-photon double ionization at 61.5 eV of neutral NH3, where the two photoelectrons and two cations are measured in coincidence using 3D momentum imaging. Three dication electronic states are identified to contribute to the N H 2 + + H + dissociation channel, where the excitation in one of the three states undergoes intersystem crossing prior to dissociation, producing a cold N H 2 + fragment. In contrast, the other two states directly dissociate, producing a ro-vibrationally excited N H 2 + fragment with roughly 1 eV of internal energy. The NH + + H + + H channel is fed by direct dissociation from three intermediate dication states, one of which is shared with the N H 2 + + H + channel. We find evidence of autoionization contributing to each of the double ionization channels. The distributions of the relative emission angle between the two photoelectrons, as well as the relative angle between the recoil axis of the molecular breakup and the polarization vector of the ionizing field, are also presented to provide insight on both the photoionization and photodissociation mechanisms for the different dication states.